2014
DOI: 10.1182/blood.v124.21.4657.4657
|View full text |Cite
|
Sign up to set email alerts
|

Final Analysis of a Phase II Study of Intrapatient Dose-Escalation of Eltrombopag in Patients Receiving Azacitidine for Myelodysplasia/AML

Abstract: Background: Pre-existing thrombocytopenia in MDS/AML is worsened during the initial cycles of azacitidine (AZA) therapy, resulting in bleeding risk and possible platelet transfusion. Eltrombopag (EPG) is an oral TPO-receptor agonist. In vitro, it has anti-proliferative effects on AML blasts. Aim: 
To assess the safety of escalated doses of EPG in patients undergoing AZA for MDS/AML Method
An investigator-initiated phase-II, single arm, study of EPG with AZA. Inclusion: relapsed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Based on our data, we could have concluded that eltrombopag and azacitidine is a safe combination. Notably, similar conclusions were drawn from two other early phase studies of azacitidine/eltrombopag in MDS/AML 12,20 . However, we are mindful that the Phase III SUPPORT study raised concerns about safety and efficacy of the combination and that patients on azacitidine should not receive eltrombopag as part of routine care.…”
Section: Discussionsupporting
confidence: 54%
“…Based on our data, we could have concluded that eltrombopag and azacitidine is a safe combination. Notably, similar conclusions were drawn from two other early phase studies of azacitidine/eltrombopag in MDS/AML 12,20 . However, we are mindful that the Phase III SUPPORT study raised concerns about safety and efficacy of the combination and that patients on azacitidine should not receive eltrombopag as part of routine care.…”
Section: Discussionsupporting
confidence: 54%
“…[15][16][17]32 There were no indicators that would predict the outcome of this phase 3 trial. 18,19 Preclinical and single-agent clinical studies of eltrombopag suggest that as a single agent, eltrombopag suppresses malignant myeloid blast proliferation [33][34][35][36] ; hence, the findings of this trial were unexpected. One hypothesis for our findings is a potential inhibition of the effects of azacitidine by eltrombopag when given concomitantly.…”
Section: Discussionmentioning
confidence: 90%
“…[15][16][17] Results of phase 1 and 2 trials have suggested that the combination of eltrombopag with azacitidine is feasible and well tolerated. 18,19 Additionally, a phase 1/2 study in lower risk MDS patients showed that the combination of another TPO-RA, romiplostim, with azacitidine was well tolerated, although blast cell counts were transiently increased in some patients. 20 Here, we report the Study of Eltrombopag in Myelodysplastic Syndromes Receiving Azacitidine (SUPPORT), a phase 3 trial investigating the efficacy and safety of eltrombopag as platelet supportive care, in patients with intermediate-to high-risk MDS and thrombocytopenia who were receiving azacitidine.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-five trials were not RCTs (Bauman 2011; Berstein 2002; Castaman 1997; Dickinson 2014; Elinoff 2014; Frey 2012; Gerrits 2015; Knoefler 2013; Kristensen 1993; Liesveld 2013; Mittelman 2012; Nash 2000; NCT00358540; NCT00472290; NCT00922883; NCT01194167; NCT01328587; NCT01500538; NCT01516619; NCT01550185; NCT01757145; NCT01791101; NCT01957176; NCT01980030; NCT02046291; NCT02323178; Olnes 2012; Palmblad 2008; Svensson 2014; Townsley 2015; Will 2009a; Will 2009b; Wolff 2001; Wu 2014; Xu 2008).…”
Section: Resultsmentioning
confidence: 99%